2019
DOI: 10.1111/jcpp.13170
|View full text |Cite
|
Sign up to set email alerts
|

The pupil: a window on social automatic processing in autism spectrum disorder children

Abstract: BackgroundFaces are crucial social stimuli, eliciting automatic processing associated with increased physiological arousal in observers. The level of arousal can be indexed by pupil diameter (the ‘Event‐Related Pupil Dilation’, ERPD). However, many parameters could influence the arousal evoked by a face and its social saliency (e.g. virtual vs. real, neutral vs. emotional, static vs. dynamic). A few studies have shown an atypical ERPD in autism spectrum disorder (ASD) patients using several kinds of faces but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 60 publications
9
46
4
Order By: Relevance
“…However, the responses of the ASD group did not differ significantly from the mental age matched TD group. Aguillon-Hernandez et al (2019) found that only dilation in response to virtual faces was stronger in ASD than in the TD group, and further confirmed the undifferentiated responses in the ASD group that were also found by Martineau et al (2011b). They hypothesise that dynamic emotional faces might elicit a larger response than static ones because of the larger emotional contagion in a dynamic or action context.…”
Section: Subject-dependent Influencessupporting
confidence: 54%
See 2 more Smart Citations
“…However, the responses of the ASD group did not differ significantly from the mental age matched TD group. Aguillon-Hernandez et al (2019) found that only dilation in response to virtual faces was stronger in ASD than in the TD group, and further confirmed the undifferentiated responses in the ASD group that were also found by Martineau et al (2011b). They hypothesise that dynamic emotional faces might elicit a larger response than static ones because of the larger emotional contagion in a dynamic or action context.…”
Section: Subject-dependent Influencessupporting
confidence: 54%
“…In their study, the ASD group showed inflexibility of regulation of the LC activity, they conclude based on a lower pupil reactivity in the presence of distractions, which is not expected when the LC would be regulated correctly. In toddlers with ASD, this LC-NE system is more often in a phasic state, which could be advantageous in a visual search task as performed by Blaser et al and could be a starting point for other cascading ASD characteristics (Blaser et al, 2014) The LC provides NE to the amygdala, thalamus and superior colliculi which are implied to be part of the low frequency face detector system, which would provide an automatic face processing (Aguillon--Hernandez et al, 2019). This system could be impaired in ASD hypothesise (Aguillon-Hernandez et al, 2019), because of their findings of reduced reactivity to faces.…”
Section: Ansmentioning
confidence: 99%
See 1 more Smart Citation
“…This could suggest that emotional faces are perceived as less appealing and less salient for children with ASD. This finding is in line with a recent pupillometry study, in which a lack of pupil dilatation was reported in children with ASD while looking at objects, as well as static and dynamic faces (54). The authors attributed this lack of difference to an insensitivity toward event-related pupil dilatation, suggesting an abnormal physiological reaction and reduced arousal to socially salient stimuli in ASD.…”
Section: Discussionsupporting
confidence: 90%
“…A recent review from Bast et al (2018) suggests that LC dysfunction might be associated with attentional differences in ASD, but there has been little prior empirical evidence to support this hypothesis. Several studies have shown phasic pupillary response differences in ASD (Martineau et al, 2011;Blaser et al, 2014;Nuske et al, 2014a,b;Krach et al, 2015;Lawson et al, 2017;Aguillon-Hernandez et al, 2019;Boxhoorn et al, 2019). However, in these studies, participants with ASD exhibited differences in task performance compared with controls; thus, differences in pupil dilations may be attributable to differences in task performance.…”
Section: Discussionmentioning
confidence: 95%